New Liberalisms for the Masses: Ontological Aristocratism and Equal Rights in José Ortega y Gasset’s La rebelión de las masas (1930) and María Zambrano’s Horizonte del liberalismo (1930) - Ryan, William J. (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
In view of the importance of mass movements and the sociopolitical crises in the early twentieth century, this article offers close readings of the liberalisms proposed in La rebelión de las masas and Horizonte del liberalismo. Ortega posits an ontological differentiation between masas and minorías excelentes based on the notion of “effort,” allowing individuals not belonging to hereditary aristocracies to ideologically appropriate aristocratic prestige. By contrast, Zambrano emphasizes the power of reform invested in the liberal subject. Although they assess the equality of rights divergently, both philosophers coincide in situating aristocratism at the core of liberalism.